Publich sports policy: The impact of the athlete schalarship programm on Brazilian men artistic gymnastics - Santos Oliveira, M.; Coelho Bortoleto, M. A. (Science of Gymnastics Journal, 2012)
The Brazilian government established the Athlete Scholarship Program, by Law no10.891/2004, aiming to contribute for athletes` economical support, development and permanence in sports and to renew the Brazilian representation in national and international competitive events. This study intends to present the program and to discuss its impact on Brazilian Men`s Artistic Gymnastics (MAG) according to the opinion of Brazilian experts. A bibliographic review has been used as methodological procedure, followed by a field survey consisting of semi-structured interviews applied to Brazilian representatives, coaches, judges and world-class gymnasts. The results revealed the important role of the Athlete Scholarship Program on the gymnasts support, however other actions are necessary to solve structural and financial problems that still affect this sport in Brazil. We suggest some changes in the program in order to increase the number of scholarships offered, to minimize the bureaucracy application and to make clearer the enrollment rules, the accountability and the selection process.